Karakteristik Kepemimpinan Melayani - Selfie Rosalina Paulus; Benny B. Binilang; Semuel Selanno (Jurnal Ilmiah Wahana Pendidikan, 2021)
The purpose of this study was to describe the application of leadership characteristics to serve as pastors. How is the understanding of the pastor and the congregation regarding the leadership to serve and the acceptance of the congregation towards the application of the characteristics of leadership serving the pastor of the existing congregation. The research method used in this research is descriptive qualitative method. In this study, data were collected through observation, interviews and documentation studies. The results of the study indicate that the pastor and the congregation have the correct understanding of servant leadership, but in practice the pastor has not fully practiced the characteristics of serving leadership which makes some congregations dissatisfied with the leadership of the existing pastor. This research is expected to provide benefits and a broader understanding for church organization leaders, pastors / pastors and congregations for the importance of implementing servant leadership in church organizations.